Pulmonary rehabilitation closer to patients – feasibility and effectiveness study - Marques, Alda (2019)
Pulmonary Rehabilitation (PR) remains highly inaccessible to patients with chronic respiratory diseases (CRD). We assessed the effects of a minimal-resource community-based PR programme in patients with CRD. Seventy-seven patients (48 male;68±11yrs;57.7±22.2%FEV1%predicted; 80.3±19.6FVC%predicted) with COPD(n=52), asthma(n=13), asthma-COPD overlap(n=3), interstitial lung disease(n=7), lung transplant due to COPD(n=1) and bronchiectasis(n=1) participated in a 12-week community-based PR programme. The modified Medical Research Council–dyspnoea scale (mMRC), Saint George’s Respiratory Questionnaire (SGRQ), quadriceps muscle strength (QMS), 1-minute sit-to-stand (1-minSTS), six-minute walk test (6MWT), Brief Balance Evaluation System Test (Brief-BESTest) and Hospital Anxiety and Depression Scale (HADS) were collected pre/post PR. Differences were examined using the Student’s t-test/Wilcoxon test and effect sizes (ES) were calculated. The number of patients improving above the minimal clinically important difference (MCID) was established, whenever a MCID was available. Significant improvements were observed (Figure 1). The number of patients above the MCID were: 33 in mMRC(1 point), 47 in SGRQ(4 points); 41 in 1min-STS(3 repetitions); 50 in the 6MWT(25m), 18 in the Brief-BESTest(4.9 points) and 32 and 28 in the HADS Anxiety and Depression scores(1.5 points). Community-based PR programmes are feasible and effective in patients with CRD.